2014
DOI: 10.5455/njppp.2014.4.011020131
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of completeness and legibility of prescription orders at a tertiary care hospital

Abstract: Background: Medication errors contribute significantly to adverse drug events. These errors can occur at any step from prescribing to administering drug. While most of the prescribing errors can be prevented, administering errors seldom can be intercepted. Aims & Objective: Prime objective was to analyze the quality of prescription writing, as a part of a continuous quality improvement program with emphasis on Completeness & legibility of prescriptions. Materials and Methods: A retrospective cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…In the prescriber information, (Figure 1) the prescriber name and signature was missing in 56% of the prescriptions, which is more than that reported by Mahato et al 22%, Patel et al 30%, but were lesser than that reported by Khan et al 77% and Dharmadikari et al 82% [18][19][20][21] The prescriber registration number was missing in 58% of the prescriptions, which is lesser as compared to the studies where it was not written in 85% and 77% of the prescriptions. [18,20] The use of personalized stamps bearing the prescribers name and registration number was found to be a useful and inexpensive method to improve the quality of the prescriptions.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…In the prescriber information, (Figure 1) the prescriber name and signature was missing in 56% of the prescriptions, which is more than that reported by Mahato et al 22%, Patel et al 30%, but were lesser than that reported by Khan et al 77% and Dharmadikari et al 82% [18][19][20][21] The prescriber registration number was missing in 58% of the prescriptions, which is lesser as compared to the studies where it was not written in 85% and 77% of the prescriptions. [18,20] The use of personalized stamps bearing the prescribers name and registration number was found to be a useful and inexpensive method to improve the quality of the prescriptions.…”
Section: Discussioncontrasting
confidence: 47%
“…[18,21,24] In this study, the students were able to select appropriate drugs for the given case scenarios, as the cases chosen were based on problems that the students had studied as part of their curriculum. The students only wrote the generic names of the drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 , 31 , 32 Legibility has been assessed using different methods including optical computer software and subjective scales, with the legibility of letter words (such as drug names) being worse than that of numbers (such as frequency of dosage). 33 , 34 , 35 A validated tool, the Prescription Quality Index (PQI), provides indicators to measure legibility in chronic diseases using a three-point Likert scale, with scores of 0 for ‘illegible’, 1 for ‘barely legible’ and 2 for ‘legible’. 36 …”
Section: Introductionmentioning
confidence: 99%